2022
DOI: 10.3390/medicina58070847
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Pitfall in Atypical Febrile Presentation in a Patient with a Pregnancy-Specific Dermatosis—Case Report and Literature Review

Abstract: Pruritic urticarial papules and plaques of pregnancy (PUPPP) usually occurs in the third trimester of pregnancy in primiparous women. It is a self-limiting inflammatory disorder with a still unknown pathogenic mechanism. The abdominal wall overdistension, with a subsequent inflammatory response due to damage to the connective tissue, represents a pathogenesis explanation. Clinical features involve intensely pruritic urticarial rash with edematous, erythematous papules and plaques. The clinical picture and derm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Some literature also reported that the publication of studies related to complement therapy to reduce nausea and vomiting during pregnancy sharply increased in the period 2007-2017. 7,8 Firstly, the top five most influential documents from studies regarding the change and treatment of the skin in pregnant women are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some literature also reported that the publication of studies related to complement therapy to reduce nausea and vomiting during pregnancy sharply increased in the period 2007-2017. 7,8 Firstly, the top five most influential documents from studies regarding the change and treatment of the skin in pregnant women are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…This shows that the number of citations per year on the document was stated to be 36.78, which it means that the document is cited an average of nearly 37 times every year from 2014 into 2022. Some documents with numerous citations studied complementary therapy to reduce nausea and vomiting during pregnancy, 7 the effect of aromatherapy on nausea and vomiting in pregnant women, 8 and the psychologic changes in pregnant women. 4 This shows that these documents have made the most contribution to the changes in pregnant women.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The associated septic symptomatology, hepatosplenomegaly, impaired liver function, pneumonia, hemolytic anemia, thrombocytopenia, and lymphocytosis have a mortality of up to 20% and serious long-term sequelae. Antiviral therapy decreases the viral load and associated organ disease [ 104 , 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…The papules can converge, forming plaques and extending to the limbs, trunk, and buttocks, protecting the mucous membranes and face ( Figure 1 ). They may exhibit small vesicles, target lesions, and polycyclic papules 14 , 22 . Generally, the condition persists for 4–6 weeks 4 .…”
Section: Polymorphic Eruption Of Pregnancymentioning
confidence: 99%